IFRS implementation and studies in Turkey - Cagnur Kaytmaz Balsari; Secil Varan (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The development of accounting system and practices in a country is a reflection of its economic development as well as legislative process. Turkey has not been an exception. Its economic development has led the accounting practices to change from tax and state oriented towards international harmonization. The purpose of this article is to provide an overview of IFRS (International Financial Reporting Standards) application in Turkey and an extensive review of IFRS related local literature gathered from major accounting, finance and business journals published in Turkey in 2005-2014 period. The local literature is expected to complement and provide insight to international literature on IFRS applications in Turkey. The findings suggest that local academic literature has been focused on application issues related to IFRS. Empirical literature findings suggest convergence problems in the application of IFRS which calls for better training and public oversight. Capital markets research findings show positive impact of IFRS adoption. Additionally, IFRS for SMEs, technical issues such as fair value measurements and convergence of tax and IFRS reporting are the important topics of discussion in local literature.
Keywords: M41; 650; IFRS studies; Turkey; accounting developments